Why executive-legislative conflict in the United States is dwindling - Peterson Paule; Greene Jay P.
An examination of executive legislative conflict occurring in US Congressional Committees between 1947 and 1990 reveals that, despite current concerns of gridlock, the overall level of conflict declined during this period. There are two structurl sources of inter-branch conflict-constituent and partisan. The constituent basis for conflict in the United States is rooted in the differing manner in which members of the two branches are elected. Because the exectutive of Congress, who have smaller, more homogeneous constituencies, are more concerned with the geographically distributive effects of these policies. The authors' evidence suggests that conflict between the executive and legislative in the United States
Keywords: Civil Service and Legislators -- U.S.A.